Phenolic Characterisation and Antioxidant Capacity of Young Wines Made From Different Grape Varieties Grown in Helanshan Donglu Wine Zone (China) - Ma, T.-T.; Sun, X.-Y.; Gao, G.-T.; Wang, X.-Y.; Liu, X.-Y.; Du, G.-R; Zhan, J.-C. (South African Journal of Enology and Viticulture, 2016)
The Helanshan Donglu wine zone (China) is one of the most successful wine region of China, and the phenolic characterisation and antioxidant capacity of the primarily young, monovarietal wines from there were evaluated. The result showed that Helanshan Donglu wines contained abundant phenolic compounds, especially flavan-3-ols, and possessed high antioxidant capacity. In different grape varieties, the phenolic profiles varied greatly in both red and white wines. For red wines, Cabernet Sauvignon represented the highest total phenols (2 631 mg/L GAE), total flavonoids (1 840.83 mg/L CTE) and antioxidant capacity. Gamay and Cabernet Gernischt possessed the highest total flavan-3-ols (1 108.08 mg/L CTE) and total anthocyanins (258.78 mg/L CGE). Amongst the white wines, Chardonnay and Chenin blanc showed the highest phenolic contents and antioxidant capacity. (+)-Catechin and (-)-epicatechin were dominant phenolic constituents in both the red and white wines. Gallic acid and salicylic acid were the second most abundant in red wines, while gentisic acid was the second most abundant in white wines.